MODEL DESA WARISAN BUDAYA: PENDEKATAN BARU DALAM KONSERVASI WARISAN BUDAYA PEDESAAN - Intan Maulida Al Barroh (BRIN, 2018)
Abstract Rural cultural heritages have great potential to develop, thus they need to be conserved. Conservation Village Model is a community program in forest conservation area that is combined and implemented in cultural heritage field and be called Cultural Heritage Village Model. This research contributes to the development of conceptual framework for cultural heritage conservation with the community engagement basis in the rural area. This research is literature research that focuses on the concept and framework of Cultural Heritage Village Model. The research stage began from collecting literatures. Analysis method used in this research is a qualitative method. This article will integrate data about Conservation Village Model and cultural heritage conservation. The result of this research is the emergence of Cultural Heritage Village Model concept including its vision and mission, basic principles, village model criteria, activity stages, activity focus, and Cultural Heritage Village Model succeed criteria.